Resurrection of Typhlops cubae Bibron, 1843 (Serpentes: Typhlopidae), with taxonomic comments on the Typhlops lumbricalis species group - Iturriaga, Manuel; Domínguez, Michel; Reynoso, Víctor Hugo (Zootaxa, 2024)
We resurrected Typhlops cubae Bibron, 1843, a species considered as a nomen dubium for the past 55 years. Based on a designated lectotype and nearly 80 additional specimens, we redescribed the species and compare it with other congeners from the Bahamas, Cuba, and Hispaniola Islands. We found that Typhlops cubae is related to the Typhlops lumbricalis species group, restricting its distribution to western Cuba and Isla de la Juventud, and overlapping with Typhlops pachyrhinus along the Pinar del Río and Artemisa provinces. We also provided additional comments about the taxonomy of other Cuban Typhlops updating their geographical distribution.